The Comparison Between the Use of Blender and 3DS Max application toward students' Comprehension of 3D Animation Subject at Vocational School in Surakarta - Prameswari, Sanchia Janita; Basori, Basori; Wihidayat, Endar Suprih (IJIE (Indonesian Journal of Informatics Education), 2019)
Based on observations at Vocational School in Surakarta, the 3 -dimensional animated subject using 3Ds Max as the only learning tool, consequently, students find it is difficult to practice during off-class as the 3Ds Max is not free software and affordable to buy by students. Blender application maybe can be compensate for 3D Max, which has a user-friendly appearance, neatly arranged, and free. The population in this study is the students of Vocational High School. The total population was 297 students.. The sample used was 70 students. The sampling technique in this study used the simple random sampling method. The data collection technique used the pretest-posttest. The data analysis technique used is the balance test, normality test, homogeneity test, and hypothesis testing using the independent sample t-test. The results of the study are as follows. First, there are differences in students’ comprehension that can be seen from the learning outcomes between the use of Blender applications (experiment class) and the 3Ds Max application (control class). Second, the effectiveness of Blender supporting applications is higher than the 3Ds Max application in improving students’ comprehension and learning outcomes. In general, it can be concluded that Blender can be used as an alternative or can replace 3Dmax as a learning medium in 3-dimensional animated subjects. This study aims to determine (1) whether there are differences between the use of Blender application and 3Ds Max on students’ comprehension; (2) a more effective supporting applications between Blender applications and 3Ds Max. This study used an experimental method with a pretest-posttest control group design model.